2014
DOI: 10.3389/fendo.2014.00012
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Seasonal Reproduction by Hypothalamic Activation of Thyroid Hormone

Abstract: Organisms living outside the tropics measure the changes in the length of the day to adapt to seasonal changes in the environment. Animals that breed during spring and summer are called long-day breeders, while those that breed during fall are called short-day breeders. Although the influence of thyroid hormone in the regulation of seasonal reproduction has been known for several decades, its precise mechanism remained unknown. Recent studies revealed that the activation of thyroid hormone within the mediobasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 93 publications
2
48
0
1
Order By: Relevance
“…Dio‐3 has been reported to show circannual changes in animals, and these changes may be relevant for the localized control of hypothalamic T3 levels . Localized changes of thyroid hormone activity in the hypothalamus may influence the seasonal differences of the hypothalamic‐pituitary responsiveness: the decrease of locally produced hypothalamic T3 concentration in winter may contribute to the TSH increase . Whether similar changes also occur in humans is not known, but the change in the sensitivity of the hypothalamus‐pituitary feedback system to FT4 levels in different seasons is compatible with this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Dio‐3 has been reported to show circannual changes in animals, and these changes may be relevant for the localized control of hypothalamic T3 levels . Localized changes of thyroid hormone activity in the hypothalamus may influence the seasonal differences of the hypothalamic‐pituitary responsiveness: the decrease of locally produced hypothalamic T3 concentration in winter may contribute to the TSH increase . Whether similar changes also occur in humans is not known, but the change in the sensitivity of the hypothalamus‐pituitary feedback system to FT4 levels in different seasons is compatible with this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant event in the last 15 years of seasonality research has been the uncovering by Yoshimura and his colleagues of the neuroendocrine pathways whereby thyroid hormones are involved in seasonality (recent reviews Yoshimura, 2013;Ikegami & Yoshimura, 2013;, Shinomiya et al, 2014. Importantly these results have been confirmed by other laboratories and extended by Yoshimura and others to mammals (reviews: Dardente et al, 2014;Ebling 2015;Stevenson & Prendergast, 2015) and fish (Nakane et al, 2013).…”
Section: The Thyroid Story: Its Molecular Basismentioning
confidence: 93%
“…More recently, it was found that thyroid-stimulating hormone secreted from the pars tuberalis of the pituitary gland is responsible for this conversion. Thyroid hormone activation enables gonadotrophin releasing hormone (GnRH) nerve terminals to directly contact the basal lamina in the portal capillary perivascular space which then activates the HPG axis [9195]. Nevertheless, it is still unclear whether molting is a direct effect of photoperiod duration or a secondary consequence of hormone levels influenced by the photoperiod, including the HPG axis, HPA (hypothalamus-pituitary-adrenal) axis and HPT (hypothalamus-pituitary-thyroid) axis (Fig.…”
Section: Seasons and Circadian Rhythmmentioning
confidence: 99%